1996
DOI: 10.1146/annurev.med.47.1.285
|View full text |Cite
|
Sign up to set email alerts
|

CLINICAL IMPLICATIONS OF THE p53 GENE

Abstract: The capacity for malignant growth is acquired by the stepwise accumulation of defects in specific genes regulating cell growth and tissue homeostasis. Although several hundred genes are known to control growth, molecular genetic studies in cancer show that few of these are consistently involved in the natural history of human cancer, and those typically in only certain types of malignancy. Prospects for development of molecular-based diagnostic and therapeutic strategies with widespread application did not loo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
90
0
6

Year Published

1997
1997
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(98 citation statements)
references
References 66 publications
2
90
0
6
Order By: Relevance
“…Candidate siRNAs were designed according to criteria outlined by siRNA sequence selector (BD Biosciences) and was based on the characterization of siRNA noted by Elbashir et al 33 The sequences 35 TTAGTGAGCCACAGTAC 51 and 652 CTCATCATGCAGCTGCTGCGAGACAAC 678 led to dramatic silence of the RACK1 or stratifin, respectively, and were used for all experiments. The nontarget siRNA used as a negative control had the scrambled gene sequence, 1 A B C D sequence was then introduced into an adenoviral genome using Adeno-X expression System 1 kit as described by manufacturer (BD Biosciences).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Candidate siRNAs were designed according to criteria outlined by siRNA sequence selector (BD Biosciences) and was based on the characterization of siRNA noted by Elbashir et al 33 The sequences 35 TTAGTGAGCCACAGTAC 51 and 652 CTCATCATGCAGCTGCTGCGAGACAAC 678 led to dramatic silence of the RACK1 or stratifin, respectively, and were used for all experiments. The nontarget siRNA used as a negative control had the scrambled gene sequence, 1 A B C D sequence was then introduced into an adenoviral genome using Adeno-X expression System 1 kit as described by manufacturer (BD Biosciences).…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4][5] Recently two new p53 homologues -p73 and p63 were identified that share strong sequence homology with key regions of p53 (see refs. [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The p53 gene has been found to be mutated in a large range of human tumours (Hollstein et al, 1991;Greenblatt et al, 1994; Sidransky and Hollstein, 1996). Many international research groups have contributed to the identification of p53 mutations and in a number of cases have correlated the presence ofp53 mutations with stage, histology, prognosis and exposure to certain environmental agents.…”
mentioning
confidence: 99%
“…11,12 Furthermore, a number of findings implicate the loss of function of the proapoptotic family member Bax in oncogenesis. [13][14][15][16][17][18] The Bax gene is inactivated in human colon cancer of the microsatellite mutator phenotype 19 and Bax-deficient cells appear resistant to cell death following activation of the Trail receptor pathway. 20 Thus, a number of lines of evidence demonstrate that decreased apoptosis because of alterations in the Bcl-2 family can promote oncogenesis.…”
Section: Introductionmentioning
confidence: 99%